Is chronic plaque psoriasis triggered by microbiota in the skin?. (8th July 2013) - Fry, L.; Baker, B.S.; Powles, A.V.; Fahlen, A.; Engstrand, L.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Psoriasis is an immune‐mediated disease involving both the innate and adaptive immune systems in genetically susceptible individuals. Microorganisms have been identified in the blood, skin and tonsils of patients with psoriasis, and beta‐haemolytic Streptococcus in the tonsils has been strongly linked to the precipitation of guttate psoriasis. Microbiota in the skin have been implicated in the immunopathogenesis of psoriasis. What does this study add? This review summarizes the current knowledge of the location and identity of, and immune response to, microorganisms in psoriasis. Based on this information, the proposal that psoriasis is triggered by microorganisms in the skin via the innate and adaptive immune systems is presented.